2008
DOI: 10.1007/s10126-008-9134-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypersalinity and Hydrogen Peroxide Upregulation of Gene Expression of Antioxidant Enzymes in Ulva fasciata Against Oxidative Stress

Abstract: The modulation of manganese superoxide dismutase (MnSOD), FeSOD, ascorbate peroxidase (APX), glutathione reductase (GR), and catalase (CAT) gene expression and activities and antioxidants in Ulva fasciata against hypersalinity (90 per thousand)-induced oxidative stress was studied. Increases in H(2)O(2) contents but no changes in lipid peroxidation and protein carbonyl group contents suggest oxidative damage did not occur in 90 per thousand condition. Antioxidants were consumed for reactive oxygen species (ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…Induction of gene transcription after exposure to stress factors has also been reported by Balestrasse et al (2008) where elevated levels of Cat transcripts occurred in soybean nodules under cadmium stress. For Ulva fasciata, Sung et al (2009) reported an increase in the amplification of Cat genes after imposed to salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of gene transcription after exposure to stress factors has also been reported by Balestrasse et al (2008) where elevated levels of Cat transcripts occurred in soybean nodules under cadmium stress. For Ulva fasciata, Sung et al (2009) reported an increase in the amplification of Cat genes after imposed to salt stress.…”
Section: Resultsmentioning
confidence: 99%
“…•− ) and hydroxyl radicals (OH − ) in macroalgae (Dring 2005;Lu et al 2006;Sung et al 2009;Kumar et al 2010;Liu & Pang 2010). The PBPs can effectively resist oxidative stress because of their nucleophilic ability to neutralize reactive oxidants (Cano-Europa et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypic plasticity in antioxidant defence system in response to a variety of stress inducers has been documented in many higher plants (Apel & Hirt, 2004). The up-regulation of antioxidant enzymes including Mn/FeSOD, APX, GR and CAT in shortterm hypersalinity (90 S A ) (Sung et al, 2009) and APX, CAT in long-term hypersalinity (Lu et al, 2006) suggested that SOD and GR are critical for Ulva fasciata against oxidative stress. In general, subtidal macroalgal species have shown more sensitive to environmental fluctuations and thus generate more ROS compared to high intertidal species.…”
Section: Ros Detoxificationmentioning
confidence: 99%
“…There are many evidences wherein antioxidant enzyme activities in marine algae have been altered in response to changes in environmental conditions (Collen & Davison, 1999 a,b;Lu, Sung, & Lee, 2006;Sung, Hsu, Wu, & Lee, 2009;Kumar & Reddy, 2012, pp. 1-160 and references therein). Further, up-regulation of FeSOD gene expression and its activity in hypersalinity were mediated specifically by H 2 O 2 , but MnSOD, APX, GR and CAT gene expression and corresponding enzyme activity were regulated by factors other than H 2 O 2 suggesting a dynamic nature of algal regulatory system in response to short-term hypersalinity that were likely changed after the long-term hypersalinity treatment (Sung et al, 2009). Higher level of antioxidant enzyme activities in intertidal U. lactuca (experiencing more harsh environmental conditions such as salinity variations and desiccation) compared to subtidal U. lactuca suggests that intertidal individuals detoxify H 2 O 2 more efficiently and are better adapted physiologically in coping with environmental stresses than subtidal individuals (Ross & Van Alstyne, 2007).…”
Section: Ros Detoxificationmentioning
confidence: 99%